Optimization of production of extracellular polymeric substances by Arthrobacter viscosus and their interaction with a 13X zeolite for the biosorption of Cr(VI) - Quintelas, C. (2011)
In this work we aimed to optimize the production of extracellular polymeric substances (EPS) by an Arthrobacter viscosus biofilm supported on 13X zeolite to be used in the biosorption of Cr(VI). The optimization parameters were agitation rate, work volume, pH and glucose concentration. Following the optimization of EPS production, the biofilm was used in the biosorption of hexavalent Cr from liquid solutions. Differences between the use of dead or active biomass and between the performance of zeolite in powder or in pellet form were also studied. The optimized EPS production allowed values of metal uptake between 2.72 mg/gbiosorbent and 7.88 mg/gbiosorbent for initial Cr(VI) concentrations of 20–60 mg/L. For an initial concentration of 20 mg/L, the optimal conditions of EPS production allowed an increase of 10% on the removal percentage of total Cr, and the use of zeolite as a powder rather than the pelleted form produced an increase of 46.5% in the removal percentage. For the initial concentration of 60 mg/L, the use of active biomass compared to dried biomass allowed a reduction of the time required for the total removal of Cr(VI) from 20 to 13 days.